A single rapid point-of-care placental growth factor determination as an aid in the diagnosis of preeclampsia - Knudsen, U; Kronborg, C; Von Dadelszen, P; Kupfer, K; Lee, S; Vittinghus, E; Allen, J; Redman, C (2012)
Objectives: To evaluate the clinical performance of a rapid point-of-care test, Triage PLGF (Alere, San Diego) in the diagnosis of preeclampsia. Study design: For the reference range 2212 plasma samples were collected from 595 subjects with normotensive pregnancies, between week 17 of gestation and delivery. In the case-control part, two cohorts of women with preeclampsia (80 women) were matched for maternal age, gestational age (GA) at sampling and parity with normotensive women who delivered at 37 weeks or more. Results: The areas under the receiver operating characteristic curves (GA < 35 weeks) were 1.0 and 0.994 (cohort 1 and 2, respectively). The clinical sensitivity of the Triage PLGF test for the pooled GA range of 21 ≤ GA < 35, using a GA dependent cut-off, was 1.0 for both cohorts with specificities of 1.0 and 0.940. Conclusions: The Triage PLGF test distinguishes well between preterm pregnancies with and without preeclampsia. © 2011 International Society for the Study of Hypertension in Pregnancy. Published by Elsevier B.V. All rights reserved.